The Study of Human Ear and its Impressions as a Means of Personal Identification: A Critical Review - Sreya Ghosh; Tina Sharma; Vaibhav Sharma; Poonam Kumari; Mahipal Singh Sankhla (Journal of Forensic Science and Medicine)
Human ear has emerged as a vital feature for personal identification and has been extensively investigated over the years. Various methodologies have been developed to utilize ear images, commonly known as ear prints, as a basis of identification. Both ear images and ear prints exhibit distinct characteristics unique to each individual, making ear features comparable in uniqueness to fingerprints. This characteristic renders the ear a potential biometric feature for future identification systems. Ear prints provide valuable information about the landmarks present in the ear, enabling comparison with the controlled ear prints or ear images obtained from the suspects at crime scenes. This review encompasses an in-depth analysis of 41 carefully selected research papers out of a pool of 152 papers that are categorized into three primary domains: ear morphology, ear identification based on surveillance camera, and ear biometric databases and algorithms. This comprehensive review consolidates the findings from a diverse range of studies in the field of ear recognition. The insights provided herein are invaluable for researchers and practitioners, fostering further advancements in ear recognition technology. The potential applications of this technology span forensic investigations and access control systems and personal identification.